2020
DOI: 10.1002/jso.26044
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes after completion thyroidectomy versus total thyroidectomy for differentiated thyroid cancer: A single‐center experience

Abstract: BackgroundThyroid cancer diagnoses are often discovered after diagnostic thyroid lobectomy. Completion thyroidectomy (CT) may be indicated for intermediate or high‐risk tumors to facilitate surveillance and/or adjuvant treatment. The completeness of thyroid resection and the safety of CT compared to total thyroidectomy (TT) is unclear. We assessed outcomes after TT or CT to determine completeness of resection and risk of complications.MethodsPatients undergoing TT or CT between 2000 and 2018 were retrospective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 17 publications
0
17
0
Order By: Relevance
“…44,45 Similar to up-front total thyroidectomy, adequate completion thyroidectomy is optimized by referral to a highvolume thyroid surgeon. 46,47 Another potential advantage of hemithyroidectomy is the possibility to remain euthyroid postoperatively. The 2015 ATA guidelines recommend maintaining TSH between 0.5 and 2 mIU/L after hemithyroidectomy for low-risk DTCs.…”
Section: Extent Of Surgerymentioning
confidence: 99%
See 1 more Smart Citation
“…44,45 Similar to up-front total thyroidectomy, adequate completion thyroidectomy is optimized by referral to a highvolume thyroid surgeon. 46,47 Another potential advantage of hemithyroidectomy is the possibility to remain euthyroid postoperatively. The 2015 ATA guidelines recommend maintaining TSH between 0.5 and 2 mIU/L after hemithyroidectomy for low-risk DTCs.…”
Section: Extent Of Surgerymentioning
confidence: 99%
“…Finally, recurrent laryngeal nerve injury and voice and swallowing dysfunction are less common after hemithyroidectomy 44,45 . Similar to up‐front total thyroidectomy, adequate completion thyroidectomy is optimized by referral to a high‐volume thyroid surgeon 46,47 …”
Section: Thyroid Cancer Diagnosis Initial Management and Stagingmentioning
confidence: 99%
“…Historically, total thyroidectomy as the initial procedure was considered to be safer than lobectomy, followed by completion thyroidectomy in terms of postoperative complications and in terms of completeness of resection of the thyroid tissue [31]. Today, however, it has been shown in many retrospective studies that completion thyroidectomy does not carry more morbidity than initial upfront total thyroidectomy and that the completeness of resection, as measured by postoperative serum Tg, is comparable as well [32][33][34][35]. In fact, several studies have even demonstrated that the rate of temporary postoperative hypoparathyroidism may be lower for completion thyroidectomy [34,35].…”
Section: Oncologic Considerations: Completion Thyroidectomy and Survivalmentioning
confidence: 99%
“…Today, however, it has been shown in many retrospective studies that completion thyroidectomy does not carry more morbidity than initial upfront total thyroidectomy and that the completeness of resection, as measured by postoperative serum Tg, is comparable as well [32][33][34][35]. In fact, several studies have even demonstrated that the rate of temporary postoperative hypoparathyroidism may be lower for completion thyroidectomy [34,35]. The question of the safety of completion lobectomy is, therefore, today, no longer an issue.…”
Section: Oncologic Considerations: Completion Thyroidectomy and Survivalmentioning
confidence: 99%
“…There is still controversy as to whether patients undergoing a completion thyroidectomy for this reason have a comparable, increased or decreased risk of complications compared to those submitted to primary thyroid surgery [16][17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%